An Analysis of Push and Pull Travel Motivations of Domestic Tourists in Nepal - Baniya, Rojan; Paudel, Kirtika (Journal of Management and Development Studies, 2016)
A rigorous analysis of tourist motivation should guide the success of marketing destinations, and the primary objective of this study is to use widely accepted ‘integrative models of push and pull motives’ to analyze travel motivations of Nepali domestic tourists. Drawing from the previous studies, investigating the direct effect of push and pull motives on domestic travel motivation, this study proposes that both push and pull motives are important determinants of domestic travel motivations, however pull factors are significantly more important than push factors for domestic travel motivations. 132 domestic travellers who travelled domestically in past six months participated in the study. One sample T-test, paired-samples T-test and mean ranking were conducted to test hypotheses. One sample T-test showed significant importance of both implicit and explicit motives, and paired sample T-test results showed pull motives are significantly more important for domestic travel motivation. Mean ranking of the constructs within pull motives showed easy access and affordability, variety seeking and history culture are top reasons for domestic travellers to visit a place. Escape daily life, seeking relaxation and sightseeing variety were top three reasons for domestic travel motivation as push motive constructs. The study’s findings unravel Nepal’s domestic tourist’s motivations, and provide practitioners and policymakers with a base to develop an effective strategy to improve the domestic tourism in Nepal.